ANALISIS FAKTOR YANG MEMPENGARUHI KEJADIAN PRETERMDI PUSKESMAS KABUPATEN BANJARNEGARA - Ratih Subekti; Lia Aria Ratmawati (Jurnal Ilmiah Medsains, 2024)
Preterm labor is labor that occurs at a gestational age of <37 weeks or 259 days from the first day of the last menstruation. The incidence of preterm labor refers to the birth of a premature baby.  The main difficulty in premature babies is care, this is due to the immaturity of the body systems and other organs to function so that it can cause complications such as respiratory distress syndrome (RDS), intraventricular bleeding, bronchopulmonary dysplasia (BPD), ductus arteriosus patem (PDA), necrotizing entero cilitis (NEC), sepsis, apnea and retinopathy of prematurity (ROP). These complications in premature babies can further increase neonatal morbidity and mortality. The aim of this research is to determine the relationship and magnitude of the risk of preterm events at the Banjarnegara Regency Health Center. The research instrument uses an observation sheet. Type of analytical survey research with a case control approach. The independent variables in this study were maternal age, gestational spacing, parity, twin pregnancy, premature rupture of membranes, antepartum bleeding, history of abortion and previous history of preterm, the dependent variable was preterm delivery. The sampling technique used the total sampling method using secondary data from 3 Community Health Centers in Banjarnegara Regency with the highest cases of preterm birth in 2023, the number of cases was 56 respondents and controls were 112 respondents. Bivariate analysis uses the chi square test. Research results show that twin pregnancies are associated with preterm events (p-value 0.043), respondents with twin pregnancies have 8.538 times the risk of experiencing preterm events compared to respondents with non-twin pregnancies (95% CI 0.931-78.298), previous preterm history was associated with preterm pregnancies. (p-value 0.04), respondents with a previous history of preterm had a 3,857 times risk of experiencing a preterm event compared to respondents who had no previous history of preterm (95% CI 1.079-13.790). Conclusion of the research is pregnancy pregnancies and a previous history of preterm are associated with the incidence of preterm at the Banjarnegara district health center.